2016
DOI: 10.1111/apm.12588
|View full text |Cite
|
Sign up to set email alerts
|

The expression of SFRP1, SFRP3, DVL1, and DVL2 proteins in testicular germ cell tumors

Abstract: Germ cell tumors of the testis are a heterogeneous group of neoplasms that affect male adolescents and young adults. Wnt signaling pathway components have been shown to be actively involved in normal and malignant germ cell differentiation and progression. In this study, we aimed to explore the expression patterns of the secreted frizzled-related protein (SFRP) and Disheveled protein family (DVL) in a subset of testicular germ cell tumors. Eighty-five formalin-fixed, paraffin-embedded tissue samples of the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…It is well know that the differentiation of ESCs into SSCs is a very complex physiological process in which multiple genes and signaling pathways are involved. A large number of findings has documented the roles of Wnt signaling, Notch signaling, and TGF‐β signaling in this process.…”
Section: Introductionmentioning
confidence: 99%
“…It is well know that the differentiation of ESCs into SSCs is a very complex physiological process in which multiple genes and signaling pathways are involved. A large number of findings has documented the roles of Wnt signaling, Notch signaling, and TGF‐β signaling in this process.…”
Section: Introductionmentioning
confidence: 99%
“…Wnt/β-catenin signaling is required for the normal development of primordial germ cells, mediated by the secreted curve-associated protein (SFRP) family, including five different glycoproteins SFRP1 to SFRP5 , and this is the largest of the Wnt signaling pathways and acts by binding directly to Wnt ligands or curl receptors [ 21 ]. Fabijanovic et al [ 22 ] showed that the expression of SFRP1 in seminomas and mixed or nonseminomas was lower in atrophied tissues compared with benign tissues, and SFRP1 appeared to be actively involved in the pathogenesis of primary testicular germ cell tumors, indicating that the downregulation of SFRP1 was actively involved in the regulation of testicular development. The results of this experiment showed that SFRP1 was negatively correlated with testicular size and development, which was similar to the regulatory conclusion of Fabijanovic, so in testicular development, SFRP1 was inferred to be involved in the negative regulation of testicular development.…”
Section: Discussionmentioning
confidence: 99%